Rebuilding Islamic Economics on New Foundations - Asad Zaman (Türkiye İslam İktisadı Dergisi)
Massive amounts of confusion exists regarding the definition of Islamic Economics. This has blocked progress in terms of the development of the discipline, since there is no agreement on what its proper subject matter and methodology is. This paper shows that the confusion arises because of our attempts to borrow foundational concepts and methodology from conventional capitalist economics. Modern economists advertise their discipline as a positive, objective, and factual science. However, it is actually a branch of moral philosophy, built on concealed moral foundations of competition, selfishness, individualism, and hedonism. Islamic economics cannot be built on such foundations. We can build the discipline of Islamic Economics on the diametrically opposite foundations of cooperation, generosity, brotherhood of mankind, and social responsibility. Instead of the methodology of Newtonian physics currently in use, we need to use the methodology of Ibne Khaldun, created for studying the process of social change. With new moral foundations, and a new methodology, it is possible to rebuild Islamic Economics on new foundations. As a first step towards doing so, we examine thirty different definitions of Economics available in the literature. We show that most of them are in harmony with our conceptualization of new foundations for the discipline. Most of the remaining can be harmonized by considering them as specialized branches of the broad definition of Islamic Economics. It is hoped that achieving consensus on goals and methods for Islamic Economics will open the path to rapid progress in the field.